ANALYSIS MACRO ECONOMIC, RISK PROFILE OF FIRM PERFORMANCE AND FIRM VALUE AT COMMERCIAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE New Normal Study After Covid Pandemic 2020-2021 - Febrianto, Gustaf Naufan; Ratnawati, Tri (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to determine the effect of Macroeconomics, Risk Profile on Company Performance and Company Value at commercial banks listed on the Indonesian stock exchange (New Normal Study after the 2020-2021 covid pandemic). The sample of this study is commercial banks listed on the IDX.This study uses a qualitative descriptive research design. The results of this study are Macroeconomics, Risk Profile and Financial Performance have an effect on Company Value at Commercial Banks Listed on the Indonesia Stock Exchange.